Propaganda dan Teori Konspirasi: Wacana Masyarakat terhadap Covid-19 di Indonesia - Akhirul Aminulloh; Myrtati Dyah Artaria; Latif Fianto; Emei Dwinanarhati Setiamandani (Universitas Merdeka Malang, 2021)
The conspiracy theory allows non-existent information to be exist. Likewise with propaganda which causes information to roll without being able to ascertain its correctness because its purpose is to manipulate public opinion. This study aims to see the complexity of the fight against the Covid-19 discourse in Indonesian society. This study used a qualitative method with a critical discourse analysis approach. Data collection was obtained from online media and social media, especially Twitter in the April 2020 period. The data were analyzed by using the Critical Discourse Analysis model of Fairclough. The result of this study indicated that it was not enough for the Covid-19 outbreak to be reported as a natural virus, but to be explored into a controversial discourse in the form of a conspiracy theory. The propaganda of the Covid-19 conspiracy theory was carried out through social media. Belief in conspiracy theory was caused by three things, they were people needed definite and reasonable answer to the phenomenon of the Covid-19 pandemic, they wanted to have control over their lives, and the impact of Post Truth era. Keywords: Propaganda, Conspiracy Theory, Discourse, Covid-19